Social and cultural determinants of traditional, complementary and integrative medicine (TCIM) use in primary care: the role of migration, health literacy, and religious orientation - G. Ciarlo; J. Buentzel; S. Grüll; J. Huebner (BMC Public Health, 2026)
Abstract Background This study examines whether migration background, health literacy, and religious–spiritual orientation are associated with the use of traditional, complementary and integrative medicine (TCIM). In addition, the relationship between religious–spiritual orientation, Religious Orientation (RO), and different TCIM modalities was explored. From a public health perspective, migration background, health literacy, and social determinants may further influence patterns of traditional, complementary and integrative medicine (TCIM) use. This study examines how religious orientation relates to the use of body–mind and biological TCIM approaches and whether these dimensions function as coping resources or determinants of health behaviour. Methods Between October 2023 and January 2024, 375 patients were recruited in a single-center primary care study. Data were collected using an anonymous questionnaire assessing TCIM use, health literacy, religious orientation, and sociodemographic characteristics. Results Of all participants, 19.5% reported a migration background. The most frequently used TCIM methods were physical activity (75.2%), vitamins and minerals (41.6%), and vitamin D (35.6%). Overall TCIM use was largely comparable between participants with and without a migration background, with a significant difference observed only for homeopathy (14.1% vs. 6.1%, p = 0.007). Participants with a migration background showed higher religious orientation scores, while specific RO were determined by religious affiliation. Health literacy levels were generally high and varied mainly by age, gender, and education, showing only weak associations with TCIM use. Female gender and higher educational level were the most consistent predictors of TCIM use. Conclusion TCIM use was common in primary care patients and showed little association with migration background or religious orientation, despite higher religiosity among migrants. Religiosity appears to function primarily as a psychosocial coping resource rather than a determinant of therapeutic behavior. From a public health perspective, TCIM use appears to be more strongly shaped by gender and educational level than by migration background or religious orientation. Female participants consistently reported higher use of several TCIM modalities, while educational level was primarily associated with lifestyle-related approaches such as physical activity. These findings underscore the importance of addressing social determinants and avoiding culturally stereotypical assumptions in primary care.